Teachers’ Evaluation of Social Studies Curriculum Contents in Reducing Moral Problems in the 21st Century Among School Students in Ibadan Metropolitan of Oyo State - Oladimeji, Taibat A.O (Scientific Trends, 2022)
This research work examines teacher’s evaluation of the adequacy of social studies contents in curbing moral problems in the 21st century among schools students in the Ibadan Metropolitan of Oyo State. The descriptive type of survey was carried out in the investigation of this study. Social Studies teachers in the Ilorin metropolis constituted the population while 104 Social Studies teachers were selected from 34 upper basic schools in the Ibadan. A questionnaire was used to collect the required data for the study. The result obtained from the finding revealed that constant lateness to school, fighting another student, cheating during the examination, dishonesty, poor attendance to classes and public display of lack of respect for teachers and administrations are some of the common immoral problems prevalent in the school. It was recommended that the school management should also put strict measures in place to curb immoral acts among the students in the school and the teachers should also put in their best behaviours to be worthy of emulations.
Keywords: Teachers, Evaluation, Social Studies, Curriculum, Contents, Moral, 21st Century and Students.